The Composition of Midgut Bacteria in Aedes aegypti (Diptera: Culicidae) That Are Naturally Susceptible or Refractory to Dengue Viruses - Coatsworth, Heather (J Insect Sci, 2018)
The composition, abundance, and diversity of midgut bacteria in mosquitoes can influence pathogen transmission. We used 16S rRNA microbiome profiling to survey midgut microbial diversity in pooled samples of laboratory colonized dengue-refractory, Cali-MIB, and dengue-susceptible, Cali-S Aedes aegypti (Linnaeus). The 16S rRNA sequences from the sugar-fed midguts of adult females clustered to 63 amplicon sequence variants (ASVs), primarily from Proteobacteria, Firmicutes, Flavobacteria, and Actinobacteria. An average of five ASVs dominated the midguts, and most ASVs were present in both Cali-MIB and Cali-S midguts. No differences in abundance were noted at any phylogenetic level (Phylum, Class, Order, Family, Genus) by analysis of composition of microbiome (w = 0). No community diversity metrics were significantly different between refractory and susceptible mosquitoes. These data suggest that phenotypic differences in the susceptibility to dengue virus between Cali-MIB and Cali-S are not likely due to major differences in midgut bacterial communities.